Applications of Marginal Abatement Cost Curve (MACC) for reducing greenhouse gas emissions: a review of methodologies - Abdullah, Lokman; Batih, Hakimul; Nur Chairat, Arief Suardi; Maslan, Mohd Nazmin (Technoscience Publications, 2022)
A wide range of Marginal Abatement Cost Curve (MACC) methods for reducing greenhouse gas (GHG) emissions has been introduced in various academic literature in the last decade to address various issues, to use different calculable logic, producing different results and implications. A detailed review has not been carried out on the application of MACC in terms of types of emissions, country/sector, and methodology used. This study is aimed at identifying, interpreting, and clarifying currently available literature on MACCs development from 2010-2020 by reviewing the previous applicability of three analytic dimensions including Greenhouse Gas (GHG) emission type, research objects, and modeling methodologies from top-down and bottom-up methods, providing researchers with information of past developments and future trends in this area. The result shows that CO2 is one of the most studied GHG emissions in calculating marginal abatement costs and some countries/regions have not received much attention from researchers in assessing emission reductions. Finally, the MACC bottom-up methodology focuses on the application of the engineering model method and the distance function method is a favorite in the application of the top-down method. Furthermore, this study also highlights possible research opportunities, which may lead to more successful and impactful results in future MACC studies.